Investigation Of Indoor Air Quality And Thermal Comfort In Mosque Buildings - Rasli, Nur Baitul Izati (2019)
The mosque is a symbolic landmark where the Muslim community mainly prays five times a day and performs other social and cultural activities. However, the widespread use of Air Conditioning Split Units (ACSUs) to cool the indoor air in mosques may pose potential adverse health effects for users. Therefore, a comprehensive investigation was conducted to identify the indoor air quality (IAQ), thermal comfort (TC), and biological contaminants (bacteria and fungi) in the typical mosque buildings in Malaysia, within different ventilation conditions (ACSUs and non-ACSUs) at lowland and highland areas. The study was conducted from 1200 h to 1700/1730 h to assess 35 mosques during Zohor-Asar and Friday-Asar prayers times. The recorded IAQ parameters were evaluated for their compliance with Malaysia’s Industrial Code of Practise (ICOP) 2010, whereas the predicted mean vote (PMV) and percentage of people dissatisfied (PPD) were used to assess thermal comfort by using the ASHRAE’s CBE thermal comfort tool. The effectiveness of ventilation strategies in reducing temperature in the main prayer halls were evaluated based on four categories: 1) roof design (Ottoman, Pyramidal, and Iran and Middle East styles), 2) ventilation conditions (ACSUs and fans), 3) window-to-wall ratio (WWR) and 4) percentage of dead walls. Next, the biological contaminant levels were also compared with ICOP’s acceptable limits and their types were identified using the ID Microgen software. Lastly, to improve IAQ and thermal comfort, the movement of outdoor air toward indoor were visualized by using the smoke flow visualization technique. The results showed that mean concentrations of indoor air contaminants (TVOC, CH2O, CO, PM10, and CO2) were still within the acceptable limits recommended by ICOP, except for the mean of O3 concentrations. The mean of O3 concentrations exceeded the acceptable limit by ICOP at 0.13±0.02 ppm (lowland ACSUs mosques) and 0.09±0.01 ppm (lowland non-ACSUs mosques) during Friday-Asar prayers. The mean indoor air contaminants of four out of six (TVOC, O3, CO, and PM10) at ACSUs mosques during Friday-Asar prayers were higher compared to non-ACSUs mosques. Moreover, based on the obtained results, the mosques at lowland (ACSUs and non-ACSUs) did not provide good thermal comfort with the highest PMV and PPD values were 1.64-2.94 and 55-99%, respectively at lowland ACSUs Pyramidal roof style mosques. Results obtained from the lowland mosques showed that the percentage of dead walls (R2=0.99) had the most effect that contributed to the high indoor air temperatures within the main prayer halls. The next factor was WWR (R2=0.72). Meanwhile, the type of roof design or ventilation condition had no significant influence on the reduction of high indoor air temperature. Furthermore, the bacteria concentrations at lowland exceeded the guideline set by the ICOP (500 cfu/m3) in ACSUs mosques (58.8%) were higher than the non-ACSUs mosques (12.5%), whereas, at highland did not. The dominant types of bacteria found in the lowland mosque were Staphylococcus spp. and Bacillus spp. whereas for fungi was Aspergillus spp. and Aspergillus niger. Meanwhile, the dominant types of bacteria found in the highland mosque were Staphylococcus spp., Bacillus spp., and Micrococci spp. whereas for fungi was Aspergillus niger and Trichoderma spp. Therefore, window panel with double pores can be implemented to allow outdoor air passing through indoor to improve better IAQ and TC in the mosques buildings.